2012
DOI: 10.3844/jcssp.2012.701.704
|View full text |Cite
|
Sign up to set email alerts
|

Features Extraction Based on Linear Regression Technique

Abstract: Problem statement:The matching problem of complex objects is one of the most difficult task in the pattern recognition field. These problems are made difficult by seemingly infinite varieties of shapes and classes which are used. The difficulties are related to absolute shape measurement, given the impossibility of directly mapping shapes, as such, into a feature space. Approach: In this study, an object was modeled using boundaries pixel distance. The invariant has been resulted from the distance of each boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Zhang et al further considered the impact of outdoor temperature and used a three-piecewise linear regression method to fit the relationship between energy consumption and outdoor temperature. However, linear regression-based methods require well-defined independent variables [31]. Brown et al predicted electricity demand using K-nearest neighborhood (KNN) in a kernel regression method [5].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al further considered the impact of outdoor temperature and used a three-piecewise linear regression method to fit the relationship between energy consumption and outdoor temperature. However, linear regression-based methods require well-defined independent variables [31]. Brown et al predicted electricity demand using K-nearest neighborhood (KNN) in a kernel regression method [5].…”
Section: Related Workmentioning
confidence: 99%
“…Clustering-based 5,6,7,9,11,12,13,14,15,16,17,18,21,30,31 Boxplot 5,6,7,9,10,11,12,13,14,15,16,17,18,19,21,30,31 Prediction-based (PARX) 5,6…”
Section: Days Of Anomalymentioning
confidence: 99%
“…Therefore, penalty function strategies do not always guarantee practical results. The advantage of linear regression is that, with the dependent variables being well defined, the technique is able to extract time series features (Magld, 2012). Lee and Fung (1997) showed that linear and nonlinear regressions can also be used for outlier detection, but they used a 5% upper and lower threshold limit for choosing outliers after fitting, which yielded many false positives for very large data sets.…”
Section: Previous Workmentioning
confidence: 99%
“…Jakkula and Cook use statistics and clustering to identify outliers in power datasets collected from smart environments [14], but they have not considered the impact of the exogenous variables, e.g., weather temperature, on the electricity consumption. Linear regression can extract time series features when the dependent variables are well-defined [31]. The early experience of identifying outliers in linear regression is through setting a threshold limit, but this yields many false positives for large data sets [18].…”
Section: Related Workmentioning
confidence: 99%